Adrenergic Mechanisms of Audiogenic Seizure-Induced Death in a Mouse Model of SCN8A Encephalopathy - Wengert, Eric R.; Wenker, Ian C.; Wagner, Elizabeth L.; Wagley, Pravin K.; Gaykema, Ronald P.; Shin, Jung-Bum; Patel, Manoj K. (Frontiers in Neuroscience, 2021)
Sudden unexpected death in epilepsy (SUDEP) is the leading cause of death amongst patients whose seizures are not adequately controlled by current therapies. Patients with SCN8A encephalopathy have an elevated risk for SUDEP. While transgenic mouse models have provided insight into the molecular mechanisms of SCN8A encephalopathy etiology, our understanding of seizure-induced death has been hampered by the inability to reliably trigger both seizures and seizure-induced death in these mice. Here, we demonstrate that mice harboring an Scn8a allele with the patient-derived mutation N1768D (D/+) are susceptible to audiogenic seizures and seizure-induced death. In adult D/+ mice, audiogenic seizures are nonfatal and have nearly identical behavioral, electrographical, and cardiorespiratory characteristics as spontaneous seizures. In contrast, at postnatal days 20-21, D/+ mice exhibit the same seizure behavior, but have a significantly higher incidence of seizure-induced death following an audiogenic seizure. Seizure-induced death was prevented by either stimulating breathing via mechanical ventilation or by acute activation of alpha-1 adrenergic receptors. Conversely, in adult D/+ mice inhibition of alpha-1 adrenergic receptors converted normally nonfatal audiogenic seizures into fatal seizures. Taken together, our studies show that in our novel audiogenic seizure-induced death model adrenergic receptor activation is necessary and sufficient for recovery of breathing and prevention of seizure-induced death.